2020
DOI: 10.2196/preprints.20044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape of COVID-19 Treatments on Media and Internet Trends: Observational Study (Preprint)

Abstract: BACKGROUND Individuals with large followings can influence public opinion and behaviours, especially during a pandemic. Recently, Donald Trump (DT) endorsed the use of unproven therapies, with a death attributed to the wrongful ingestion of a chloroquine-containing compound. OBJECTIVE We investigated his speeches, his twitter, Google searches and purchases, Amazon purchases, and TV airtime for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…11 Trump's social media presence and voice alone elicited an amplification cascade across media outlets, garnering 300% more impression reach than his usual tweets and more than 2% of airtime of conservative networks. 12 In turn, purchases of hydroxychloroquine and its analogs surged on Amazon by over 200%. 13 Another study showed a grim and strong correlation between the degree of approval of Donald Trump and the case fatality rate associated with the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Trump's social media presence and voice alone elicited an amplification cascade across media outlets, garnering 300% more impression reach than his usual tweets and more than 2% of airtime of conservative networks. 12 In turn, purchases of hydroxychloroquine and its analogs surged on Amazon by over 200%. 13 Another study showed a grim and strong correlation between the degree of approval of Donald Trump and the case fatality rate associated with the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…12 In turn, purchases of hydroxychloroquine and its analogs surged on Amazon by over 200%. 13 Another study showed a grim and strong correlation between the degree of approval of Donald Trump and the case fatality rate associated with the COVID-19 pandemic. 14 While these statistics are shocking, blame mustn't be placed on the public.…”
Section: Introductionmentioning
confidence: 99%